Immunological and non-immunological effects of stem cell-derived extracellular vesicles on the ischaemic brain. (24th July 2018) - Doeppner, Thorsten R.; Bähr, Mathias; Giebel, Bernd; Hermann, Dirk M.
Following the implementation of thrombolysis and endovascular recanalization strategies, stroke therapy has profoundly changed in recent years. In spite of these advancements, a considerable proportion of stroke patients still exhibit functional impairment in the long run, increasing the need for adjuvant therapies that promote neurological recovery. Stem cell therapies have initially attracted great interest in the stroke field, since there were hopes that transplanted cells may allow for the replacement of lost cells. After the recognition that transplanted cells integrate poorly into existing neural networks and that they induce brain remodelling in a paracrine way by secreting a heterogeneous group of nanovesicles, these extracellular vesicles (EVs) have been identified as key players that mediate restorative effects of stem and progenitor cells in ischaemic brain tissue. We herein review restorative effects of EVs in stroke models and discuss immunological and non-immunological mechanisms that may underlie recovery of function.